An Integrated Model To Analyse Policy Process: A Case Study Of Malaysia’s National Biotechnology Policy - Mahalingam, Ravi (2010)

(untitled)
Biotechnology is one of the major technologies of the twenty-first century and in fact is the fastest growing sectors in the world. It is a fascinating field that has been identified as the next engine of growth for Malaysia, one that will deliver economic gains through research and development, creation of entrepreneurial opportunities for industrial growth, improvement of food security, health and environmental sustainability. Realising the important contributions of biotechnology to the country, this research seeks to examine the policymaking process of National Biotechnology Policy, which is aimed to provide a structured guideline in developing the industry.